2020
DOI: 10.3390/molecules25112605
|View full text |Cite
|
Sign up to set email alerts
|

Osteomeles schwerinae Extract and Its Major Compounds Inhibit Methylglyoxal-Induced Apoptosis in Human Retinal Pigment Epithelial Cells

Abstract: The accumulation and formation of advanced glycation end products (AGEs) are related to diabetes and age-related disease. Osteomeles schwerinae C. K. Schneid. (Rosaceae, OSSC) is used traditionally for the treatment of various diseases in Asia. Previous studies have shown that OSSC elicits preventive effects in an in vivo model of diabetes. This study was to evaluate the antiapoptotic effects of dried leaves and twigs of OSSC extract and its major compounds in ARPE-19 cells—spontaneously arising human retinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Depletion of GSH suppresses the Glo1 function and induces significant MGO accumulation [54] . Several reports have proved that MGO induces apoptosis in cells, including HK-2 cells [55] , rat INS-1 pancreatic β-cells [56] and human retinal pigment epithelial cells [57] . Our results confirmed that MGO can also induce apoptosis in HLECs.…”
Section: Potential Mechanism For the Effect Of Aluas Rna On Mgo-cause...mentioning
confidence: 99%
“…Depletion of GSH suppresses the Glo1 function and induces significant MGO accumulation [54] . Several reports have proved that MGO induces apoptosis in cells, including HK-2 cells [55] , rat INS-1 pancreatic β-cells [56] and human retinal pigment epithelial cells [57] . Our results confirmed that MGO can also induce apoptosis in HLECs.…”
Section: Potential Mechanism For the Effect Of Aluas Rna On Mgo-cause...mentioning
confidence: 99%
“…Although the underlying mechanisms have not been completely uncovered, advanced glycation end‐products (AGEs) and reactive oxygen species (ROS) have been demonstrated to be closely associated with the pathogenesis of DR. [ 2–4 ] Production of ROS and AGEs has been reported to lead to oxidative stress and inflammatory responses via multiple cellular signaling pathways, thereby inducing injury of the retina. [ 5–7 ] A recent study confirmed that the loss of pericyte selection was an important early event in the pathogenesis of DR. Accumulation of AGEs in the pericytes can trigger the production of ROS, in turn inducing activation of caspase‐3 that initiates the apoptosis process.…”
Section: Introductionmentioning
confidence: 99%
“…Aster koraiensis extract prevents retinal pericyte apoptosis in streptozotocin (STZ)-induced diabetic rats [ 13 ]. Osteomeles schweinae extract inhibits methylglyoxal (an active precursor in the formation of AGEs)-induced apoptosis in human retinal pigment epithelial cells [ 14 ]. Cinnamomi Ramulus (the twig of Cinnamomum cassia Blume; Lauraceae) and Paeoniae Radix (the root of Paeonia lactiflora Pallas; Paeoniaceae) have been shown to exert efficacy in inhibiting the formation of AGEs in our previous study.…”
Section: Introductionmentioning
confidence: 99%